Regulatory mechanisms of tetramethylpyrazine on central nervous system diseases: A review - Yue Liu; Guang Yang; Wenqiang Cui; Wenqiang Cui; Yunling Zhang; Xiao Liang (Frontiers Media S.A., 2022)
Central nervous system (CNS) diseases can lead to motor, sensory, speech, cognitive dysfunction, and sometimes even death. These diseases are recognized to cause a substantial socio-economic impact on a global scale. Tetramethylpyrazine (TMP) is one of the main active ingredients extracted from the Chinese herbal medicine Ligusticum striatum DC. (Chuan Xiong). Many in vivo and in vitro studies have demonstrated that TMP has a certain role in the treatment of CNS diseases through inhibiting calcium ion overload and glutamate excitotoxicity, anti-oxidative/nitrification stress, mitigating inflammatory response, anti-apoptosis, protecting the integrity of the blood-brain barrier (BBB) and facilitating synaptic plasticity. In this review, we summarize the roles and mechanisms of action of TMP on ischemic cerebrovascular disease, spinal cord injury, Parkinson's disease, Alzheimer's disease, cognitive impairments, migraine, and depression. Our review will provide new insights into the clinical applications of TMP and the development of novel therapeutics.